PEMBERDAYAAN EKONOMI MASYARAKAT DESA LEBAKSARI MELALUI PENGOLAHAN PELEPAH PISANG MENJADI PRODUK INOVATIF - Manshur, Ahmad; Al-Bari, Akhmad; Izza, Yogi Prana; Hidayat, Nur Maulana; Ningsih, Wita (Universitas Padjadjaran, 2025)
Lebaksari Village, located in Bojonegoro Regency, has strong agricultural potential. One of its main strengths is the abundant growth of banana trees, planted both as primary crops and as a means to utilize unused land. Although banana pseudostems have the potential to be processed into higher-value products, their use has been limited to making ropes with low economic value. To enhance the value of local products, a community service program using the Asset-Based Community Development (ABCD) method was implemented. The program followed five stages: discovery, dream, design, define, and destiny. Technical training was provided to members of the PKK women’s group and local artisans. The training focused on producing innovative crafts from banana pseudostems, such as bags and jewelry. For sustainability, the initiative was entrusted to the PKK group through their regular meetings, with support from Lebaksari village officials. The products are expected to be marketed through local bazaars and social media platforms, with a sales target of at least 1.25 times the production cost to boost household income through creative industries. A qualitative evaluation revealed high enthusiasm and active participation, as shown by the number of questions raised. The program successfully improved community knowledge and skills. Participants demonstrated the ability to identify good-quality raw materials, apply innovative crafting techniques, and produce products that meet performance criteria such as neatness, functionality, and marketability. This initiative lays the foundation for a self-sustaining creative economy in Lebaksari, reflecting the success of knowledge transfer and community empowerment.Desa Lebaksari yang terletak di Kabupaten Bojonegoro memiliki potensi besar di bidang pertanian. Salah satu keunggulan desa ini adalah keberadaan pohon pisang yang banyak ditanam, baik sebagai tanaman utama maupun untuk memanfaatkan lahan kosong. Meskipun pelepah dari pohon pisang memiliki potensi untuk diolah menjadi produk bernilai tambah, namun pemanfaatannya di desa ini masih terbatas pada pembuatan tali yang memiliki nilai ekonomi rendah. Untuk meningkatkan nilai produk lokal, program pengabdian masyarakat menggunakan metode Asset-Based Community Development (ABCD) maka dilaksanakan. Tahapan program mencakup discovery, dream, design, define, dan destiny. Pelatihan teknis diberikan kepada anggota PKK dan pengrajin lokal, berfokus pada pembuatan kerajinan inovatif dari pelepah pisang seperti tas dan perhiasan. Untuk keberlanjutan program maka program kemudian dititipkan melalui ibu PKK melaui pertemuan rutinnya serta dukungan pejabat desa lebaksari. Produk diharapkan dapat dipasarkan lewat bazar lokal dan media sosial, dengan target omzet minimal 1,25 kali dari biaya produksi. Produk-produk ini diharapkan dapat dipasarkan melalui bazar lokal dan media sosial untuk meningkatkan pendapatan masyarakat melalui ekonomi kreatif. Evaluasi kualitatif menunjukkan antusiasme dan partisipasi aktif peserta yang tinggi, terlihat dari banyaknya pertanyaan yang diajukan. Program ini berhasil meningkatkan pengetahuan dan keterampilan masyarakat, dibuktikan dengan kemampuan peserta dalam mengidentifikasi bahan baku pelepah pisang, menerapkan teknik produksi inovatif, serta menghasilkan produk yang memenuhi kriteria unjuk kerja seperti kerapihan, fungsionalitas, dan nilai jual.